The mechanistic role of gitogenin as a treatment for laryngeal cancer: a network pharmacology and experimental analysis - Fu, Zhuo; Guan, Yue; Hu, Zhangwei (Frontiers in Pharmacology, 2025)
ObjectiveLaryngeal cancer (LC) is a significant and persistent therapeutic challenge worldwide. Gitogenin (GIT), a naturally occurring saponin, has demonstrated anticancer activity in lung cancer. However, its potential effects on LC remain unclear. This study aimed to elucidate the therapeutic efficacy of GIT and the mechanisms through which it acts against LC by integrating network pharmacology analysis with experimental validation.MethodsPotential targets of GIT were established using the PharmMapper database, while LC-associated genes were retrieved from the GeneCards database. Common targets between GIT and LC were determined, and the top 20 genes were chosen for protein-protein and gene-gene interaction (PPI and GGI) network construction. Functional enrichment analyses were conducted. Finally, in vitro experiments were performed to validate how GIT affects LC.ResultsA total of 96 putative GIT targets for LC were identified. KEGG enrichment identified the PI3K-Akt axis a key regulatory mechanism. In vitro experiments provided confirmation that GIT inhibited LC cell proliferation, viability, migratory activity, and invasion ability by modulating PI3K-Akt signaling.ConclusionUsing network pharmacology and experimental validation, it was demonstrated that GIT exerts potent anticancer effects on LC by targeting the PI3K-Akt axis. The present findings suggest the potential of GIT for treating LC.